2020
DOI: 10.1038/s41598-020-77769-6
|View full text |Cite
|
Sign up to set email alerts
|

Design, reliability and construct validity of a Knowledge, Attitude and Practice questionnaire on personal use of antibiotics in Spain

Abstract: Numerous questionnaires are available on Knowledge, Attitudes, and Practices (KAP) towards antibiotics' use by adults, but none of these questionnaires is fully validated. We undertook an exhaustive literature review to design a comprehensive KAP questionnaire concerning the personal use of antibiotics in Galicia, North Spain. The Item Content Validity Index (I-CVI) and modified Kappa statistic (K*), confirmed the content validity of the questions (0.78 ≤ I-CVI ≤ 1.00 and 0.78 ≤ K* ≤ 1.00). The S-CVI statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…This is in agreement with findings from other studies elsewhere. [ 45 47 ] On the other hand, some other studies observed varying practice levels from 49.6% to 57.3%. [ 36 38 40 ] The difference between our study and these other studies may not be unrelated to the fact that ours was among health workers while these others were from community-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with findings from other studies elsewhere. [ 45 47 ] On the other hand, some other studies observed varying practice levels from 49.6% to 57.3%. [ 36 38 40 ] The difference between our study and these other studies may not be unrelated to the fact that ours was among health workers while these others were from community-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…The previously validated KAP questionnaire on antibiotic use by the general population [ 10 ], was translated forward and backward into Arabic and French by native multilingual researchers (see Supplementary Files S1 and S2 online ). The translated questionnaire was then fully validated in 2019 in Lebanon in a population of adults.…”
Section: Methodsmentioning
confidence: 99%
“…French is also the first teaching language in 70% of primary schools in Lebanon [ 15 ]. The English version of the questionnaire is published elsewhere [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations